Ultrastructural Localization of the α4-Subunit of the Neuronal Acetylcholine Nicotinic Receptor in the Rat Substantia Nigra - Arroyo-Jiménez, Maria del Mar (J Neurosci, 1999)
The distribution of the α4-subunit of the neuronal nicotinic acetylcholine receptor (nAChR) in the rat brain was examined at light and electron microscopy levels using immunohistochemical staining. In the present study we demonstrate the specificity, in both tissue homogenates and brain sections, of a polyclonal antibody raised against the rat nAChR α4-subunit. The characterization of this antibody involved: (1) Western blot analysis of rat brain homogenates and membrane extracts from cells previously transfected with diverse combinations of neuronal nAChR subunits, and (2) immunohistochemistry using transfected cells and rat brain tissue. At the light microscope level, the α4-subunit-like-immunoreactivity (LI) was widely distributed in the rat brain and matched the distribution of the α4-subunit transcripts observed previously by in situhybridization. Strong immunohistochemical labeling was detected in the mesencephalic dopaminergic nuclei. The nAChRs in this region are thought to be responsible for the modulation of dopaminergic transmission. The neurotransmitter identity of α4-immunolabeled neurons in the substantia nigra pars compacta (SNpc) and the ventral tegmental area was thus assessed by investigating the possible colocalization of the nAChR α4-subunit with tyrosine hydroxylase using confocal microscopy. The double labeling experiments unambiguously indicated that the α4-subunit-LI is present in dopaminergic neurons. At the electron microscope level, the neurons in the SNpc exhibited α4-subunit-LI in association with a minority of postsynaptic densities, suggesting that the α4-subunit may be a component of functional nAChRs mediating synaptic transmission between midbrain cholinergic neurons and mesencephalic dopaminergic neurons.